Spontaneous remission of acute myeloid leukemia with NF1 alteration. (2020) - Bradley, Terrence; Zuquello, Radames Adamo; Aguirre, Luis E.; Mackrides, Nicholas; Chapman, Jennifer; Cimmino, Luisa; Thomassen, Amber; Watts, Justin
Abstract: Acute myeloid leukemia (AML) is defined by the presence of ≥ 20% myeloblasts in the blood or bone marrow. Spontaneous remission (SR) of AML is a rare event, with few cases described in the literature. SR is generally associated with recovery from an infectious or immunologic process, and more recently possibly with clonal hematopoiesis. We review the literature and assess the trends associated with SR, and report a new case of a 58-year-old man with a morphologic diagnosis of AML associated with a severe gastrointestinal (GI) tract infection. The patient had an NF1 variant that was previously unreported in AML as the only clonal abnormality. After treatment of the infection, the increased blast population subsided with no leukemia-directed therapy, and the patient has remained in a continuous, spontaneous complete remission for > 2 years.